ANALISIS YURIDIS KEWENANGAN KOMISI PEMBERANTASAN KORUPSI DALAM PENYIDIKAN PELAKU TINDAK PIDANA KORUPSI PENGADAAN ALAT UTAMA SISTEM SENJATA OLEH OKNUM TENTARA NASIONAL INDONESIA - Ardiansyah, Andri; Jayakusuma, Zulfikar; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The Corruption Eradication Commission is an independent institution specifically formed to handle corruption cases that are equipped with a set of authority in carrying out the tasks of investigation, investigation and prosecution.In carrying out the duties and authority of the Corruption Eradication Commission in conducting investigations of the perpetrators of corruption, the procurement of the main equipment of the weapons system clashes with the oath of soldiers and the Military Justice Law, which has led to pros and cons in various circles.The purpose of writing this thesis is; first, to find out the authority of the Corruption Eradication Commission in investigating the perpetrators of corruption in the procurement of the main weapons system, especially those carried out by the Indonesian National Armed Forces.second, to find out the criminal law policy on the authority of the Corruption Eradication Commission in investigating perpetrators of corruption in the procurement of the main weapons system by the Indonesian National Armed Forces.In writing this thesis the author uses the normative juridical research method that emphasizes legal principles, namely the principle of legality. Then analyzed qualitatively and then make conclusions with the deductive method.The results of the author's research, are; First, the Investigation carried out by the Corruption Eradication Commission has a legal basis Article 42 of Law Number 30 of 2002 concerning the Corruption Eradication Commission.All authorities related to investigations, investigations and prosecutions as stipulated in Law Number 8 of 1981 concerning Criminal Procedure Law also apply to investigators, investigators, and public prosecutors in the Corruption Eradication Commission.Criminal law policy towards the handling carried out by the KPK and the Military related to the corruption case of the procurement of defense equipment is a separate treatment.Finally, the authors submit a suggestion that the President together with the House of Representatives (DPR) need to establish a regulation regarding the procedures and procedures regarding the investigation or existing laws must be amended so that there is no error in the authority of the investigation by any institution including the KPK, and so that the implementation or implementation the investigation has a clear legal umbrella and has legal jurisdiction.Keywords: Investigation - Corruption Crime - Military